Quality Education In the Qur’anic Perspective and the Sustainable Development Goals, the Fourth Goal, as Model (an analytical Study) (Journal of the College of Basic Education, 2025)
The research focuses on good education because education in today’s world has an impact on knowledge creation, skills acquisition, and community service. The research approaches the concept of education from the Qur’anic perspective, distinguishes between teaching and learning, and lists the quality elements on which good education is based to achieve its goalsQuality education is a fourth goal of the Sustainable Development Goals 2015-2030 Therefore, the research shed light on the definition of sustainable development. The research relied on various sources that contributed to developing a set of results and recommendations